Private Finance for Development : Wishful Thinking or Thinking Out of the Box? - Devine, Hilary (Departmental Papers; Departmental Paper ;, 2021)
The Covid-19 pandemic has aggravated the tension between large development needs in infrastructure and scarce public resources. To alleviate this tension and promote a strong and job-rich recovery from the crisis, Africa needs to mobilize more financing from and to the private sector.